CAPABILITY OF INDONESIA’S CREATIVE INDUSTRY IN THE ERA OF ASEAN ECONOMIC COMMUNITY (AEC) - Afida Kurnia Yogasari (HI 16 UMY 116, 2016)
*116 The creative industry nearly developed fast. Officially established since 2005, Indonesia should have proper preparation towards the creative industry, especially while facing the regional economic cooperation such as ASEAN Economic Community (AEC) in 2015. There is still less understanding about the Indonesia’s government preparation towards the creative industry, especially before competing in the era of ASEAN Economic Community (AEC). Here Indonesia used the RPJM 1 and 2 as the set of plan, to be more prepared comparing with other ASEAN member countries like Singapore, Malaysia and Thailand.